Segmental Language Changes And Phoneme Comparison Developments - Nurkhaliza, Intan Siti; Umry, Al Aini; Lubis , Yani (CV. Generasi Insan Rafflesia, 2023)
communication that people use to express their feelings and thoughts to others. One linguistic subsystem is sound. In linguistics, these elements are often called phonemes. Phoneme is the smallest linguistic unit that can distinguish meaning. It should be understood that the sounds of the language are very important for the speaker to be able to understand what is being expressed or expressed by other speakers in the communication network. It is often difficult to understand the language of a speaker whose pronunciation is unclear. In fact, serious misunderstandings often occur due to unclear pronunciation. This study aims to (1) describe the characteristics of Indonesian segmental phonemes. (2) Describe the characteristics of segmental phonemes in Javanese. (3) Explain the difference between Indonesian and English segmental phoneme features.